The ghosts of Monday / [videorecording (DVD)] - Sands, Julian; Huberman, Mark, 1981-; Trill, Elva; Marouchou, Christina (Cleopatra Entertainment, 2023)
It tells the chilling story of a group of US film-makers who travel to Cyprus to film a documentary in the tragically famous Hotel Gula a once popular resort where more than 100 people died in mysterious circumstances. What begins as just another day at the office will eventually turn into a terrifying journey into the unknown.